Radiation response on the Nb/MgO interface with different interface angles. (March 2021) - Du, J.L.; Chen, H.Q.; Wu, Z.M.; Wang, Y.F.; Yan, Y.; Yang, K.J.; Liu, Z.L.; Zhang, J.; Fu, E.G.
Highlights: Width of He bubble denuded zones at Nb/MgO interface is related to interface angle. One-dimensional linear differential equation model is modified to study its mechanism. Interface angle influences sink ability of Nb/MgO interface to radiation damage. Abstract: Heterophase interfaces have been considered as effective sinks for radiation induced defects and impurities in nuclear materials. However, the quantitative correlation of interface structure and the ability of interface sinking radiation damage is still largely elusive. In this study, we found that the interface angle plays important role in determining interface's sink ability to radiation damage. Their correlations were investigated by performing He ion irradiation on the Nb film with column grain structure grown on single crystal MgO(1 0 0) substrate and we found that the sink efficiency of Nb/MgO interface is related to the interface angle. Considering the dependence of a He atom's diffusion direction on interface angle, one-dimensional linear differential equation model was corrected by a structure factor to understand the mechanisms for the influence of interface angle on the sink efficiency of Nb/MgO interfaces, and the sink efficiencies of Nb/MgO interface with different interface angles were well predicted by the corrected model. This study could provide novel insights and mechanisms for further understanding the role of interface structure in enhancing radiation tolerance.